Design and modelling of four-legged amphibious robot - Masood, Alnajar; Eldin, Muhammad Saad; Omar, Bnhamdoon; Syafiq, Muhammad; Toha @ Tohara, Siti Fauziah; Abu Hanifah, Rabiatuladawiah (Kansai University, 2020)
This paper proposed a method to model the gait movement of four-legged amphibious robot. This type of robot has shown a great potential to perform complex operations in difficult and challenging land and underwater environments. Not only they can monitor and manipulate complicated environment conditions during disasters such as floods, landslides, and others, but it can also perform deep ocean exploration, underwater structures manipulation, disaster rescue operations, and reconnaissance. The promising advantages of amphibious underwater robots have motivated researchers to propose different design strategies for the structures and control methods of such vehicles. To design and model the fourlegged amphibious robot, the connection between the input links with the output links was identified in this paper. The system architecture and system prototype were developed for model performance test. The tests were conducted and analyses using the SAM- the Ultimate Mechanism Designer for various configurations of the links in terms of the angle, angular velocity and the angular acceleration.